Characterization of Immune Cell Subset Expansion in Response to Therapeutic Treatment in Mice - Tomala, Jakub; Spangler, Jamie B (Methods in molecular biology, 2020)
Flow cytometry has revolutionized the field of molecular immunology, enabling the monitoring and characterization of immune events at the single-cell level. Here, we describe a flow cytometry-based workflow to quantify the activation of specific immune cell subsets in mice in response to a molecular intervention. Compared to laborious long-term disease models, this technique allows for relatively rapid evaluation of candidate therapeutics designed to elicit a targeted immune response. This approach has the range to address both disease applications in which an immunostimulatory effect would be desired (e.g., cancer, infectious disease) or those in which an immunosuppressive effect would be desired (e.g., autoimmune disorders, transplantation medicine). Overall, our technique presents a powerful and accessible strategy for preliminary in vivo assessment of potential immunotherapeutics.
Keywords: Animals; myši transgenní; analýza jednotlivých buněk; Ovalbumin; průtoková cytometrie; Mice, Transgenic; Neoplasms; nádory; převzatá imunita; CD8-Positive T-Lymphocytes; Flow Cytometry; Adoptive Transfer; Mice; myši; Immunophenotyping; Workflow; imunofenotypizace; CD8-pozitivní T-lymfocyty; CD4-Positive T-Lymphocytes; zvířata; Single-Cell Analysis; průběh práce; ovalbumin; CD4-pozitivní T-lymfocyty